Sports Nutrition and Gross Motor Skill Development in Youth Athletes: A Literature Review - Setyo Purwanto; Yovhandra Ockta (Postgraduate, University of Mataram, 2024)
This study explores the relationship between sports nutrition and gross motor skill development in young athletes, focusing on maintaining optimal nutrition levels. The primary issue identified is the lack of understanding of how nutrition impacts gross motor skills and athletic performance in children and adolescents. This study explores the relationship between sports nutrition and gross motor skill development in young athletes. The study aims to analyze how nutritional strategies affect gross motor skill development and overall health in young athletes. A qualitative descriptive research model, informed by a comprehensive literature review, was used. Literature was collected from reputable scientific databases using keywords such as